Solution of the mixed integer large scale unit commitment problem by means of a continuous Stochastic linear programming model - Siface, D.; Vespucci, M. T.; Gelmini, A. (Energy systems (Berlin. Periodical), 2014)
Power Systems all around the World faced in the last decade a large increase of penetration of power generation produced by Renewable Energy Sources, a large part of which (in particular wind generation and solar generation) is affected by high levels of uncertainty. Being Renewable Energy Sources only partially controllable all this uncertainty is transferred into Power System operation. Thus, numerical simulation of Power Systems needs to be able to cope with this uncertainty, that is Stochastic Programming techniques have to be considered. Anyway, numerical simulation of Power Systems also involves a very large number of variables, some of which are of integer nature: a large scale mixed integer stochastic problem has thus to be solved, but the requirement in computational power and time could reveal to be far too large. Thus, heuristic procedures must be introduced. In this paper it is introduced the sMTSIM model, based on a Stochastic continuous relaxation of the mixed integer Unit Commitment problem and on an heuristic procedure capable of re-introducing the mixed integer constraints.